Web-Based Information System for Managing Savings and Loans at the Mera Ndi Ate Cooperative - Marlince Kadobo; Ardiyanto Dapadeda; Dian Fransiska Ledi (International Journal Software Engineering and Computer Science (IJSECS), 2026)
A web-based cooperative information system — accessible at any time via the internet — allows administrators and members to retrieve real-time financial data, automate transaction recording, generate periodic reports, and monitor loan and deposit statuses with measurable accuracy. At the Mera Ndi Ate Cooperative, however, member registration and financial data management are still conducted manually through ledger entries, producing recurring problems: duplicate records, transcription errors, vulnerability to physical data loss, slow reporting cycles, and underutilized computing infrastructure. A web-based system was therefore developed to support daily operations, accelerate service delivery, reduce recording errors, and improve financial transparency. The study adopted a descriptive qualitative approach and applied the Waterfall model as the system development methodology. The resulting Mera Ndi Ate Cooperative Information System covers the full operational cycle — from member registration to financial reporting — and is supported by a real-time dashboard connected to a centralized database that tracks deposits, loans, and installment payments. The system measurably improves data accuracy, access speed, and operational accountability, while also strengthening the cooperative's capacity for long-term financial governance.